Vitamin D Levels in Active TB, Latent TB, Non-TB Pneumonia and Healthy Children: A Prospective Observational Study. (3rd September 2018) - Buonsenso, Danilo; Sali, Michela; Pata, Davide; Masiello, Enrico; Salerno, Gilda; Ceccarelli, Manuela; Delogu, Giovanni; Valentini, Piero
Abstract: Background : Growing evidence suggests that vitamin D deficiency might be implicated in the development of active tuberculosis (TB). We evaluated vitamin D levels in children with active TB compared to children with latent TB infection (LTBI), non-TB pneumonia (NTBP) and healthy controls to determine if there was a difference. Methods : In this prospective study, vitamin D levels were measured and compared between the four groups and adjusted for age, ethnicity, gender and season of sample collection. Results : Fifty-seven children were included: 24.6% active TB, 28.1% LTBI, 22.8% NPTB and 24.6% healthy controls. 36.8% of all children tested had an insufficient or deficient vitamin D level. Vitamin D level was significantly lower in active TB compared to other groups ( p = 0.004). Conclusions : Our study showed a correlation between hypovitaminosis D and active pulmonary TB.